Prevalence of metallo-β-lactamase-encoding genes among carbapenem-resistant Pseudomonas aeruginosa strains isolated from burn patients in Iran - Jabalameli,Fereshteh (2018)
Abstract Carbapenem-resistant Pseudomonas aeruginosa (CRPA) has been considered a major cause of infection and mortality in burn patients, especially in developing countries such as Iran. One of the most common mechanisms of carbapenem resistance is production of metallo-β-lactamases [(MBLs), including Verona Integron-encoded Metallo-beta-lactamase (VIM), imipenemase (IMP), São Paulo metalo-beta-lactamase (SPM), German imipenemase (GIM), New Delhi metallo-beta-lactamase (NDM), Dutch imipenemase (DIM), Adelaide imipenemase (AIM), Seoul imipenemase (SIM), KHM, Serratia metallo-β-lactamase (SMB), Tripoli metallo-β-lactamase (TMB), and Florence imipenemase (FIM)]. Limited information is available on the prevalence of CRPA and MBLs in Iranian burn units. We performed a systematic search by using different electronic databases, including Medline (via PubMed), Embase, Web of Science, and Iranian Database. Of 586 articles published from January 2000 to December 2016, 14 studies reporting the incidence of CRPA and MBLs as detected by molecular methods in burn patients were included in this review. The meta-analyses showed that the prevalence of CRPA, IMP, and VIM was 76.8% (95% CI 67.5-84.1), 13.1% (95% CI 4.7-31.5), and 21.4% (95% CI 14.6-30.1), respectively, in Iranian burn centers and remaining MBLs types have not yet been detected. There was a high prevalence of MBLs and CRPA in Iranian burn centers. Therefore, these measurements should be applied nationally and rigorous infection control measures and antimicrobial stewardship will be the major pillars to control multidrug resistant microorganisms, such as CRPA.